Application of the Think Talk Write Learning Model to Improve Argumentation Skills on Ecosystem Materials - Jamilah Solihah; R. Ading Pramadi; Meti Maspupah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Biology learning at the high school level is still dominated by traditional learning which has not yet developed thinking/argumentation skills. This study aims to analyze the increase in students' argumentation skills after applying the Think Talk Write learning model to Ecosystem material. The researcher uses a research method that is pre-experimental design and uses a quantitative and qualitative approach, namely quantitative data obtained based on pretest and posttest analysis while qualitative data is obtained through observation and questionnaires. Analysis of the quality of student arguments was carried out using the N-Gain test, the average value during the pretest was 48.41 and the posttest was 75.34 with an average N-Gain value obtained 0.52. It can be concluded that the results of the analysis that has been carried out on the application of the TTW learning model in improving argumentation skills have a positive effect so that they can be used effectively in the classroom